(untitled) (Journal of Engineering, 2012)
In this work, the effect of variation of semi-angle of the conical part on the vibration characteristics of cylindrical-conical coupled structure is investigated. The shell is made of polyester resin reinforced by continuous E-glass fibers. The case is analyzed experimentally and numerically for orthotropic shell structures. The experimental program is conducted by exciting the fabricated structure by an impact hammer and monitoring the response using an attached accelerometer for different semi-angles of the conical part. Software named SIGVIEW is used to perform the signal processing on the acquired signal in order to measure the natural frequencies and the corresponding mode shapes. The numerical investigation is achieved using ANSYS (Finite Element software) which was verified by the experimental results. Good agreement is achieved when comparing the experimental and numerical results. The maximum deviation in results was found to be (5.9%). The maximum relative nodal rotational and translational amplitudes associated with the first normal mode of the orthotropic and isotropic shells are noted for the structure of semi-angle of cone of 45o .